The role of depressive symptoms and symptom dimensions in actigraphy-assessed sleep, circadian rhythm, and physical activity - Difrancesco, Sonia; Penninx, Brenda W. J.H.; Riese, Harriëtte; Giltay, Erik J.; Lamers, Femke (Psychological medicine, 2022)
Considering the heterogeneity of depression, distinct depressive symptom dimensions may be differentially associated with more objective actigraphy-based estimates of physical activity (PA), sleep and circadian rhythm (CR). We examined the association between PA, sleep, and CR assessed with actigraphy and symptom dimensions (i.e. mood/cognition, somatic/vegetative, sleep). Fourteen-day actigraphy data of 359 participants were obtained from the Netherlands Study of Depression and Anxiety. PA, sleep, and CR estimates included gross motor activity (GMA), sleep duration (SD), sleep efficiency (SE), relative amplitude between daytime and night-time activity (RA) and sleep midpoint. The 30-item Inventory of Depressive Symptomatology was used to assess depressive symptoms, which were categorised in three depression dimensions: mood/cognition, somatic/vegetative, and sleep. GMA and RA were negatively associated with higher score on all three symptom dimensions: mood/cognition (GMA: = -0.155, < 0.001; RA: = -0.116, = 0.002), somatic/vegetative (GMA: = -0.165, < 0.001; RA: = -0.133, < 0.001), sleep (GMA: = -0.169, < 0.001; RA: = -0.190, < 0.001). The association with sleep was more pronounced for two depression dimensions: longer SD was linked to somatic/vegetative ( = 0.115, = 0.015) dimension and lower SE was linked to sleep ( = -0.101, = 0.011) dimension. As three symptom dimensions were associated with actigraphy-based low PA and dampened CR, these seem to be general indicators of depression. Sleep disturbances appeared more linked to the somatic/vegetative and sleep dimensions; the effectiveness of sleep interventions in patients reporting somatic/vegetative symptoms may be explored, as well as the potential of actigraphy to monitor treatment response to such interventions.